Performance evaluation of 3D rotating anode in electro coagulation reactor: Part II: Effect of rotation. (October 2017) - Choudhary, Aditya; Mathur, Sanjay
Highlights: Hydrodynamics of proposed reactor configuration was studied via CFD and RTD. Lower short circuiting index when mixing is done via anode rotation. Experimental results are in accordance with CFD simulations. CFD simulations show that mass transfer increases with increase in anode rotation speed. CFD has shown the influence of the hydrodynamic regime on the process efficiency. Flow is always turbulent when mixing is introduced via anode rotation. Anode rotation improves the color and COD removal efficiency with less energy consumption in the proposed reactor configuration. Abstract: A hopper bottom electro chemical reactor with rotating 3D anode is attempted to avoid commonly encountered problems in electrochemical reactor like short circuiting, development of dead zones, formation of oxide layer on anode surface etc. The RTD experiments and CFD simulations established that the present configuration is free from these operational difficulties. The simulated synthetic textile wastewater is treated in the proposed configuration. A higher COD removal efficiency (96.40%), color removal efficiency (99.88%) and low specific energy consumption (0.028 J/mg) are observed vis-à-vis stationary 3D anode reactor.